2010
DOI: 10.1001/archoto.2010.216
|View full text |Cite
|
Sign up to set email alerts
|

Transoral Robotic-Assisted Surgery for Head and Neck Squamous Cell Carcinoma

Abstract: the 2-year functional and oncologic results justify the continued treatment of select patients with head and neck squamous cell carcinoma with robotic-assisted surgical resection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
89
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 111 publications
(106 citation statements)
references
References 41 publications
16
89
0
1
Order By: Relevance
“…Meanwhile, the 18-month recurrence-free survival rates were 78 % (for both groups) while the 2-year rates were 79 and 86.3 %, respectively. These early figures compared favorably to existing reports of OPC treated with chemoradiotherapy [24][25][26][27] yet the functional outcomes associated with transoral approaches are significantly better than chemoradiotherapy.…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 56%
See 2 more Smart Citations
“…Meanwhile, the 18-month recurrence-free survival rates were 78 % (for both groups) while the 2-year rates were 79 and 86.3 %, respectively. These early figures compared favorably to existing reports of OPC treated with chemoradiotherapy [24][25][26][27] yet the functional outcomes associated with transoral approaches are significantly better than chemoradiotherapy.…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 56%
“…The oncologic outcomes from TORS surgery for oropharyngeal cancer (OPC) are slowly emerging, and early outcomes seem promising [24][25][26][27]. In the studies to date, local failure rates vary between 0 and 3 %, with median follow-up rates ranging from 18 to 24 months [24][25][26][27].…”
Section: Surgical Options For Treatment Of Opsccmentioning
confidence: 99%
See 1 more Smart Citation
“…More than twenty studies on TORS in animals, cadavers, human subjects and various head and neck cancer sites have been published since 2005 [1][2][3][4]. A Pubmed search revealed several prospective studies based on series of at least 20 patients in the United States [5][6][7][8][9][10][11][12][13] and Australia [14] but only one European series [15] has been published in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…1 Previous studies have demonstrated its feasibility, lower morbidity rates, good functional outcomes, and comparable overall survival rates for patients with upper aerodigestive tract neoplasms. [2][3][4][5] With the introduction of any new technology or novel operative technique is an anticipated learning curve. As new institutions incorporate TORS into their everyday practice, it is helpful to have a timeline reference of expected goals to follow as their experience increases.…”
mentioning
confidence: 99%